PENGARUH SUKU BUNGA, NILAI TUKAR, DPK, DAN NPF/NPL KPR TERHADAP PENYALURAN KPR PERBANKAN DI INDONESIA - Muchammad Atho'ur Rohman; Siti Zulaikha (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the effect of interest rates, exchange rates, third party funds and NPF / NPL Mortgages on the distribution of banking mortgages in Indonesia. It is intended that Islamic banks are able to make optimal policies in the distribution of mortgages and mitigation so that the Islamic banking market share can develop. The data required is secondary data from the Indonesian Banking Statistics report, Islamic Banking Statistics, and Indonesian Economic and Financial Statistics for the period October 2014 - May 2019. Based on Multiple Linear Regression, it is known that the simultaneous test results of all variables together have a positive significant effect in the distribution of banking mortgages, and in the partial test it is known that the interest rates and third party funds have a significant positive effect on mortgages in sharia and conventional banking. The exchange rate has a significant positive effect on Islamic banking mortgages, and a significant negative effect on conventional banking mortgages. NPF / NPL mortgage has an insignificant positive effect on the mortgages of both banks. So it can be concluded that the variable interest rates, exchange rates, and third party funds affect the distribution of Islamic banking mortgages and conventional banking mortgages, while the variable NPF / NPL mortgages have no effect.Keywords: Interest rates, exchange rates, third party fund, non performing finance, non performing loan